2015
DOI: 10.3109/13561820.2014.1003802
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional communication failures in acute care chains: How can we identify the causes?

Abstract: Although communication failures between professionals in acute care delivery occur, explanations for these failures remain unclear. We aim to gain a deeper understanding of interprofessional communication failures by assessing two different explanations for them. A multiple case study containing six cases (i.e. acute care chains) was carried out in which semi-structured interviews, physical artifacts and archival records were used for data collection. Data were entered into matrices and the pattern-matching te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…These interprofessional challenges are not unique to the ED, and poor communication and lack of cohesion between providers leading to limitations in definitive decision-making occur across the healthcare system. [42][43][44] However, our study found that these barriers to effective teamwork appear to exacerbate safety threats when patients present with acute agitation. A recently published framework for interprofessional collaboration cited structured team process and dynamic delegation of roles/responsibilities as core concepts for effective healthcare teams, as reflected in our study findings.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These interprofessional challenges are not unique to the ED, and poor communication and lack of cohesion between providers leading to limitations in definitive decision-making occur across the healthcare system. [42][43][44] However, our study found that these barriers to effective teamwork appear to exacerbate safety threats when patients present with acute agitation. A recently published framework for interprofessional collaboration cited structured team process and dynamic delegation of roles/responsibilities as core concepts for effective healthcare teams, as reflected in our study findings.…”
Section: Discussionmentioning
confidence: 66%
“…Staff expressed a need for enhanced coordination among healthcare team members during an agitated patient encounter, but noted barriers to teamwork due to silos and hierarchy causing antagonism between providers of different professions. These interprofessional challenges are not unique to the ED, and poor communication and lack of cohesion between providers leading to limitations in definitive decision‐making occur across the healthcare system . However, our study found that these barriers to effective teamwork appear to exacerbate safety threats when patients present with acute agitation.…”
Section: Discussionmentioning
confidence: 72%
“…We defined the chain of emergency care as: the interprofessional structure in which emergency care is delivered by multiple providers with the aim to provide seamless care to patients with acute care needs. 6 …”
Section: Introductionmentioning
confidence: 99%
“…IPCP occurring “when multiple health workers from different professional backgrounds provide comprehensive services by working with patients, their families, carers and communities to deliver the highest quality of care across settings” [5] has been identified as a key element to address these challenges. Shortcomings in collaboration between various health professions have repeatedly been linked to care failures, problems in work processes and patient safety [1], [2], [4]. Consequently health policy leaders across the globe have called for the use of IPCP as a key approach to improve the quality and safety of patient care [5], [6], [7], [8].…”
Section: Project Descriptionmentioning
confidence: 99%
“…Failure to deliver efficient interprofessional collaborative practice (IPCP) has repeatedly been linked to deficits in care and impaired patient-safety [1], [2], [3], [4]. Consequently, health policy makers across the globe have called for the use of IPCP to improve quality and safety of care and address the upcoming challenges to health services [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%